Management of Ganglion: Comparative Study between Surgical Excision and Aspiration followed by Intralesional Steroid Injection - Uddin, Md Nasir; Rahman, Munshi Md Mojibur; Rahman, Md Mahbubur; Hossain, SM Shakhwat (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Ganglions are tense, smooth, cystic transilluminant swellings. They are the commonest soft tissue swelling of the hand and most commonly found on the dorsum of the wrist. At present aspiration or surgery are the management options of Ganglion. To improve the outcome of treatment some advocated aspiration combined with steroid injection into the cyst. Objectives: To compare pain relief, cosmetic results and recurrence rate in the management of ganglion with aspiration followed by intralesional steroid (triamcinolone acetate) injection and surgical excision. Materials and Methods: Prospective interventional control trial was performed from October 2016 to October 2017. Fifty patients were treated in two groups in group A (33 patients), aspiration followed by intralesional steroid (triamcinolone acetate) injection and group B (17 patients) surgical excision was performed on. Follow up of patients were done on at one, three and six months after treatment up to 1 year. Results: In group A out of 33 patients, pain relief was in all 33 (100%) patients, there was no scar mark and only in 4 (12.12%) patients there was recurrence which was managed by repeating the procedure. In group B, out of 17 patients, pain relief was in 15 (88.23%), 17(100%) patients had linear scar mark, 1(5.8%) patient had hypertrophic scar and 02 (11.76%) patients had recurrence which was managed with intralesional steroid as group A. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 190-192